ANALYSIS AND ASSESSMENT OF PERSONNEL CAPACITY OF THE ORGANIZATION’S STAFF AT PRESENT STAGE - V. Ya. Afanasyev; N. V. Vorontsov; O. V. Baykova (Вестник университета, 2020)
The existing methods and approaches for analysing an organization’s personnel capacity have been considered, a retrospective review of the well-known classifications of Russian scientists has been carried out. The authors have studied the papers devoted to the practical aspects of assessing the personnel capacity of industrial enterprises in the context of a number of areas, including: personnel management, sustainable development management, increasing the competitiveness and market value of a company. A new approach to analysing personnel capacity has been proposed in the form of assessment of personnel security or the current level of personnel risks, which are, in turn, attributed to such components of personnel capacity as qualification / working experience, ability / speed of reproduction of labor resources.